Advances in Delay Differential Equations - Kashchenko, Alexandra (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint contains the 11 articles published in the Special Issue "Advances in Delay Differential Equations" of the MDPI journal Mathematics. The papers cover a wide range of topics connected to the theory of differential equations with delay. These topics include, among others, the construction of solutions, analytical and numerical methods for; dynamical properties of; and applications of DDE to the mathematical modeling of various phenomena and processes in physics, biology, ecology, and medicine. It is hoped that the reprint will be interesting and useful for those working in the area of differential equations with delays and nonlinear dynamics, as well as for those with the proper mathematical background who are willing to become familiar with recent advances in mathematical modelling, which have now entered almost all areas of science.